Protective effects of scutellarin on superoxide-induced oxidative stress in rat cortical synaptosomes - Liu Hong; Yang Xiang-Liang; Wang Ying; Tang Xiao-Qiao; Jiang Dong-Ying; Xu Hui-Bi (Acta Pharmacologica Sinica, 2016)
AIM: To evaluate the effects of scutellarin on superoxide-induced oxidative stress in rat cortical synaptosomes. METHODS: Oxidative damage model was established by incubation with xanthine (0.3 mmol/L) and xanthine oxidase (0.02 U) at 37 degree for 30 min. The extent of membrane oxidation was assessed by malondialdehyde (MDA). Membrane fluidity was measured by fluorescence anisotropy (polarization) of the lipophilic probe 1,6-diphenyl-1,3,5-hexatriene (DPH). Intracellular Ca2+ concentration([Ca2+]i) was measured by fluorescent spectrophotometry. Fura 2-AM was used as an indicator for [Ca2+]i. Na+/K+-ATPase activity assay was based on the amount of inorganic phosphate (Pi) released during an enzymatic hydrolysis of ATP. RESULTS: Synaptosomes exposed to superoxide significantly elevated the levels of malondialdehyde (MDA) and [Ca2+]i compared with those in normal group. These changes were accompanied by the decrease in membrane fluidity and Na+/K+-ATPase activity. Pretreatment with scutellarin (25-100 micromol/L) significantly ameliorated the oxidative damage of synaptosomes by reducing MDA levels and [Ca2+]i, up-regulating membrane fluidity and restoring Na+/K+-ATPase activity. CONCLUSION: Scutellarin exerts a potent protective effect against oxidative damage in synaptosomes induced by superoxide.